Prevalence of Schistosoma haematobium infection among students at Al-Agali Islamic complex in Al-Kalakela area, Khartoum State-Sudan - Abdalla, Eltagi A. M.; Youssouf, Adnan M. A.; Ahmed, Babiker M. H. (International Journal Of Community Medicine And Public Health, 2020)
Background: In Sudan, urinary schistosomiasis caused by S. haematobium is endemic in many areas of the country, mainly among school-age children. The study was done with the aim to determine the prevalence and possible risk factors of S. haematobium among students at Al-Agali Islamic complex in Al-Kalakla- Sudan. Methods: A total of 102 students were participated. 10 ml of urine sample was taken from each participant, the samples were allowing it to sediment, a drop from sediment was taken and examined microscopically using x40 objective to identify S. haematobium. A structured questionnaire was used to collect data on socio-demographic characteristics and some risk factors. The data were analyzed used SPSS version20. Chi-square test was used to determine the significance differences between variables. The Odds ratio (OR) was applied with 95% CI. Results: The prevalence of S. haematobium among students was 12.7% (13/102). The results showed there was no statistical association between socio-demographic variables (Age group, parents’ education, monthly family income and family size) and S. haematobium positivity (p>0.05). Bivariate analysis showed; swimming in rivers (OR= 8.09, 95% CI=1.69-38.73, p=0.008), working in agriculture (OR= 4.42, 95% CI=1.25-15.55, p=0.020), past infection of S. haematobium (OR=4.87, 95% CI= 1.44- 16.45, P=0.010), pre-schistosoma treatment (OR=10.29, 95% CI=2.14-49.39, p=0.003) and don not knew mode of transmission (OR=10.72, 95% CI=1.33-86.01, p=0.025), statistically significant with S. hameatobium positivity. Conclusion: The S. haematobium is still prevalent among students in study area. Health education on the mode of transmission, possible risk factors and prevention is recommended.